Verifiable attribute-based searchable encryption scheme based on blockchain - Xixi YAN; Xiaohan YUAN; Yongli TANG; Yanli CHEN (Tongxin xuebao)
For the problem that the shared decryption key lacks of fine-grained access control and the search results lacks of correctness verification under one-to-many search model,a verifiable attribute-based searchable encryption scheme based on blockchain was proposed.The ciphertext policy attribute-based encryption mechanism was used on the shared key to achieve fine-grained access control.Ethereum blockchain technology was combined to solve the problem of incorrect search results returned by the semi-honest and curious cloud server model,so it could prompt both the cloud server and the user to follow the rules of the contract honestly and achieved service-payment fairness between the user and the cloud server in the pay-per-use cloud environment.In addition,based on the irreversible modification of the blockchain,the cloud server was guaranteed to receive the service fee,and the user was assured to obtain the correct retrieval results without additional verification which reduced the computational overhead of the user.The security analysis shows that the scheme satisfies the semantic security against adaptive chosen keyword attack and can protect the privacy of users and the security of data.The performance comparison and experimental results show that the scheme has certain optimizations in security index generation,search token generation,retrieval efficiency and transaction quantity,so it is more suitable for one-to-many search scenarios such as smart medical.